Respuesta :
Answer:
A) 1.55
B) 1.55
C) 12.92
D) 34.08
E) 57.82
Explanation:
The free body diagram attached, R is the radius of the wheel
Block B is lighter than block A so block A will move upward while A downward with the same acceleration. Since no snipping will occur, the wheel rotates in clockwise direction.
At the centre of the whee, torque due to B is given by
[tex]{\tau _2} = - {T_{\rm{B}}}R[/tex]
Similarly, torque due to A is given by
[tex]{\tau _1} = {T_{\rm{A}}}R [/tex]
The sum of torque at the pivot is given by
[tex]\tau = {\tau _1} + {\tau _2}[/tex]
Replacing [tex]{\tau _1}[/tex] and [tex]{\tau _2}[/tex] by [tex]{T_{\rm{A}}}R [/tex] and [tex]- {T_{\rm{B}}}R[/tex] respectively yields
[tex]\begin{array}{c}\\\tau = {T_{\rm{A}}}R - {T_{\rm{B}}}R\\\\ = \left( {{T_{\rm{A}}} - {T_{\rm{B}}}} \right)R\\\end{array} [/tex]
Substituting [tex]I\alpha[/tex] for [tex]\tau[/tex] in the equation [tex]\tau = \left( {{T_{\rm{A}}} - {T_{\rm{B}}}} \right)R[/tex]
[tex]I\alpha=\left( {{T_{\rm{A}}} - {T_{\rm{B}}}} \right)R[/tex]
[tex]\frac{I\alpha}{R} =\left {{T_{\rm{A}}} - {T_{\rm{B}}}} \right[/tex]
The angular acceleration of the wheel is given by [tex]\alpha = \frac{a}{R}[/tex]
where a is the linear acceleration
Substituting [tex]\frac{a}{R} [/tex] for [tex]\alpha[/tex] into equation
[tex]\frac{I\alpha}{R} =\left {{T_{\rm{A}}} - {T_{\rm{B}}}} \right[/tex] we obtain
[tex]\frac{Ia}{R^2} =\left {{T_{\rm{A}}} - {T_{\rm{B}}}} \right[/tex]
Net force on block A is
[tex]{F_{\rm{A}}} = {m_{\rm{A}}}g - {T_{\rm{A}}}[/tex]
Net force on block B is
[tex]{F_{\rm{B}}} = {T_{\rm{B}}} - {m_{\rm{B}}}g[/tex]
Where g is acceleration due to gravity
Substituting [tex]{m_{\rm{B}}}a[/tex] and [tex]{m_{\rm{A}}}a[/tex] for [tex]{F_{\rm{B}}}[/tex] and [tex]{F_{\rm{A}}}[/tex] respectively into equation [tex]\frac{Ia}{R^2} =\left {{T_{\rm{A}}} - {T_{\rm{B}}}} \right[/tex] and making a the subject we obtain
[tex] \begin{array}{c}\\{m_{\rm{A}}}g - {m_{\rm{A}}}a - \left( {{m_{\rm{B}}}g + {m_{\rm{B}}}a} \right) = \frac{{Ia}}{{{R^2}}}\\\\\left( {{m_{\rm{A}}} - {m_{\rm{B}}}} \right)g - \left( {{m_{\rm{A}}} + {m_{\rm{B}}}} \right)a = \frac{{Ia}}{{{R^2}}}\\\\\left( {{m_{\rm{A}}} + {m_{\rm{B}}} + \frac{I}{{{R^2}}}} \right)a = \left( {{m_{\rm{A}}} - {m_{\rm{B}}}} \right)g\\\\a = \frac{{\left( {{m_{\rm{A}}} - {m_{\rm{B}}}} \right)g}}{{\left( {{m_{\rm{A}}} + {m_{\rm{B}}} + \frac{I}{{{R^2}}}} \right)}}\\\end{array}[/tex]
Since [tex] {m_{\rm{B}}}[/tex] = 3kg and [tex] {m_{\rm{B}}}[/tex] = 7kg
g=9.81 and R=0.12m, I=0.22[tex]{\rm{ kg}} \cdot {{\rm{m}}^2}[/tex]
Substituting these we obtain
[tex]a = \frac{{\left( {{m_{\rm{A}}} - {m_{\rm{B}}}} \right)g}}{{\left( {{m_{\rm{A}}} + {m_{\rm{B}}} + \frac{I}{{{R^2}}}} \right)}}[/tex]
[tex]\begin{array}{c}\\a = \frac{{\left( {7{\rm{ kg}} - 3{\rm{ kg}}} \right)\left( {9.81{\rm{ m/}}{{\rm{s}}^2}} \right)}}{{\left( {7{\rm{ kg}} + 3{\rm{ kg}} + \frac{{0.22{\rm{ kg/}}{{\rm{m}}^2}}}{{{{\left( {0.120{\rm{ m}}} \right)}^2}}}} \right)}}\\\\ = 1.55235{\rm{ m/}}{{\rm{s}}^2}\\\end{array} [/tex]
Therefore, the linear acceleration of block A is 1.55 [tex]{\rm{ m/}}{{\rm{s}}^2}[/tex]
(B)
For block B
[tex]{a_{\rm{B}}} = {a_{\rm{A}}}[/tex]
Therefore, the acceleration of both blocks A and B are same
1.55 [tex]{\rm{ m/}}{{\rm{s}}^2}[/tex]
(C)
The angular acceleration is [tex]\alpha = \frac{a}{R}[/tex]
[tex]\begin{array}{c}\\\alpha = \frac{{1.55{\rm{ m/}}{{\rm{s}}^2}}}{{0.120{\rm{ m}}}}\\\\ = 12.92{\rm{ rad/}}{{\rm{s}}^2}\\\end{array}[/tex]
(D)
Tension on left side of cord is calculated using
[tex]\begin{array}{c}\\{T_{\rm{B}}} = {m_{\rm{B}}}g + {m_{\rm{B}}}a\\\\ = {m_{\rm{B}}}\left( {g + a} \right)\\\end{array}[/tex]
[tex]\begin{array}{c}\\{T_{\rm{B}}} = \left( {3{\rm{ kg}}} \right)\left( {9.81{\rm{ m/}}{{\rm{s}}^2} + 1.55{\rm{ m/}}{{\rm{s}}^2}} \right)\\\\ = 34.08{\rm{ N}}\\\end{array}[/tex]
(E)
Tension on right side of cord is calculated using
[tex]\begin{array}{c}\\{T_{\rm{A}}} = {m_{\rm{A}}}g - {m_{\rm{A}}}a\\\\ = {m_{\rm{A}}}\left( {g - a} \right)\\\end{array}[/tex]
[tex]\begin{array}{c}\\{T_{\rm{A}}} = \left( {7{\rm{ kg}}} \right)\left( {9.81{\rm{ m/}}{{\rm{s}}^2} – 1.55{\rm{ m/}}{{\rm{s}}^2}} \right)\\\\ = 57.82{\rm{ N}}\\\end{array}[/tex]
![Ver imagen opudodennis](https://us-static.z-dn.net/files/d93/5a49274083b1c39c8a51a9cbc326ec09.png)